A representação do jornalista nas histórias em quadrinhos: Cyberpunk e novo jornalismo numa leitura crítica de Transmetropolitan - Souza, Alexandro Carlos de Borges (2013)
Journalists, as an interpretative comunity, or tribe, define themselves through social traces and the mastery of pratical knowledges which allow them to claim an especific professional field. This journalistic culture is also rich of myths and social representations that try to legitimate the role played by the journalist into society. These myths very often cover their professional reality. Born in the papers, the modern comics have a tradition in represent journalists as comic characters. This representation, especially in superheroes, adventure and similar comics, has served to strenght the professional image passed by the myths. But, through time, as comics have narrative and themathically matured themselves, this representation has been problematized, unmasking the ideology behind the myths. This research tries to show this phenomenon through a study of case about a comic book called Transmetropolitan. This comic shows the adventures of a journalist called Spider Jerusalem, who lives at a chaotic metropolis in search of his stories. Our work was divided in two parts. The first one is a bibliographical review about themes that this study is based upon. In the second, it was made a content analysis of three editions of Transmetropolitan, and the data was used to guide our critical review of the comic. We argue that this comic book brings a contracultural vision about contemporary society and the role of the journalist, supported by the cyberpunk narrative and the style of report used by New Journalism to problematize this myths.